Cover Feature: Regulated Drug Release Abilities of Calcium Carbonate–Gelatin Hybrid Nanocarriers Fabricated via a Self‐Organizational Process (ChemMedChem 19/2017). (9th October 2017) - Murai, Kazuki; Kurumisawa, Kazuya; Nomura, Yoshihiro; Matsumoto, Mutsuyoshi
Abstract : The Cover Feature shows the drug releasing of a calcium carbonate–gelatin hybrid nanocarrier fabricated through a single process using biomimetic mineralization. Gelatin can act not only as a binding site for anionic drugs but also as a site of nucleus formation for calcium carbonate mineralization. We found that under neutral and basic conditions, drug release from the nanocarrier was inhibited, whereas under acidic conditions, the drug was efficiently released. In addition, the drug release profile could be controlled by alternately shifting the pH values. More information can be found in the Full Paper by Kazuki Murai et al. onpage 1595 in Issue 19, 2017 (DOI:10.1002/cmdc.201700358 ).